2021
DOI: 10.3390/cancers13102411
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Reactive Oxygen Species Metabolism to Induce Myeloma Cell Death

Abstract: Multiple myeloma (MM) is a common hematological disease characterized by the accumulation of clonal malignant plasma cells in the bone marrow. Over the past two decades, new therapeutic strategies have significantly improved the treatment outcome and patients survival. Nevertheless, most MM patients relapse underlying the need of new therapeutic approaches. Plasma cells are prone to produce large amounts of immunoglobulins causing the production of intracellular ROS. Although adapted to high level of ROS, MM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 223 publications
(294 reference statements)
2
28
0
Order By: Relevance
“…Our previous data supported the interest to promote an oxidative stress in an anti-MM strategy [18]. In particular, increasing ROS to high levels may provide a unique tool to kill myeloma cells [28]. Indeed, we recently reported that modulating the redox balance of MM cells could be an effective therapy for refractory or post-treatment patients [18].…”
Section: Discussionsupporting
confidence: 61%
“…Our previous data supported the interest to promote an oxidative stress in an anti-MM strategy [18]. In particular, increasing ROS to high levels may provide a unique tool to kill myeloma cells [28]. Indeed, we recently reported that modulating the redox balance of MM cells could be an effective therapy for refractory or post-treatment patients [18].…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies have reported that some of oxysterols, including 5,6-Epoxycholesterol isomers and 25-HC, induce cell death through the death receptor-mediated extrinsic and mitochondria-dependent intrinsic apoptosis pathways [ 19 , 41 ]. Especially mitochondria-dependent intrinsic apoptosis is closely associated with the loss of mitochondrial membrane potential (ΔΨm) that is resulted in mitochondrial membrane permeabilization and the production of ROS [ 41 , 42 ]. Sequentially, highly increasing ROS also act as inducers of apoptotic cell death in various types of cells, including fibroblast cells [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially mitochondria-dependent intrinsic apoptosis is closely associated with the loss of mitochondrial membrane potential (ΔΨm) that is resulted in mitochondrial membrane permeabilization and the production of ROS [ 41 , 42 ]. Sequentially, highly increasing ROS also act as inducers of apoptotic cell death in various types of cells, including fibroblast cells [ 41 , 42 , 43 ]. In addition, the increasing ROS induce the increase of autophagosome [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since multiple myeloma cells also express high levels of Kv1.3 [22] (also see https://www. proteinatlas.org/ENSG00000177272-KCNA3/single+cell+type (accessed on 25 February 2022) for RPMI-8226) and are characterized by high intracellular ROS levels [23], here we investigated the effects of these novel Kv1.3 inhibitors on different multiple myeloma cell lines as well as in patient-derived primary multiple myeloma cells.…”
Section: Introductionmentioning
confidence: 99%